Setting Regulatory Limits for Sulphur Content in Premium Motor Spirit (PMS): A Case of Degraded Vehicles - , Terry Henshaw; , Ify L. Nwaogazie (Archives of Current Research International, 2017)
The need for a cleaner environment free from unhealthy levels of Sulphur IV oxide (SO2) has prompted this study of setting regulatory limits of sulphur content in Premium Motor Spirit (PMS) especially that used in Nigeria. This study has used secondary and primary data to show the extent of damage to the environment, caused by high sulphur content in the PMS we use especially with degraded vehicles. The method adopted for this studyinvolved field monitoring at three number locations (Choba junction, Rumuokoro junction and Alakahia off the East-west road), to obtain meteorological parameters via installed weather stations, traffic count through positioned Close Circuit Television (CCTV) cameras and sampled vehicular exhaust emission of SO2 from randomly selected vehicles. Results showed that vehicles using PMS distributed in Nigeria emits as high as 210.6 mg/m3 and as low as 0.0 mg/m3 SO2 from their exhausts. For the Department of Petroleum Resources (DPR) and the Ministry of Environment (MENv) to achieve its environmental limit of 0.15 mg/m3ambient level of SO2, they need to reduce the sulphur content limit in PMS supplied to Nigeria to 0.01% weight or restrict the movement of vehicles that emit more than 30.6mg/m3 SO2(degraded vehicles) from their exhausts.